2011
DOI: 10.1007/s11237-011-9171-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical activation of freons and their joint conversion with sulfur and carbon dioxides

Abstract: FOREWORDWe begin this paper by celebrating the 75th birthday of the important physical chemist and excellent human, our instructor and teacher, Academician of the National Academy of Sciences of Ukraine, Vice-President of the National Academy of Sciences of Ukraine, and honored director of the L. V. Pisarzhevskii Institute of Physical Chemistry of the National Academy of Sciences of Ukraine, V. D. Pokhodenko, with whom it has been my good fortune to work for more than 40 years, beginning at the student's bench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Work conducted in our laboratory involved the catalytic degradation of CFC-113 in the presence of electrogenerated cobalt(I) salen [39] in a DMF-TBABF 4 medium saturated with CO 2 ; recently, we have finished an unpublished study pertaining to the use of electrogenerated nickel(I) salen in DMF-TBABF 4 saturated with CO 2 . Like the results found by Titov et al [37], negligible amounts of carboxylic acids were detected upon reduction of this vicinal CFC, but higher yields of more dechlorinated products (HFC-1132 and HFC-1132a) were obtained; these observations suggest the possibility that CO 2 mediates electron transfer to cause more effective cleavage of carbon-chlorine bonds. Direct reduction of CFC-113 in the presence of CO 2 at a glassy carbon cathode gives rise to a single cathodic peak, as opposed to the two peaks recorded for direct reduction of CFC-113 in the absence of CO 2 .…”
Section: B Catalytic Reduction Of Cfcs With Electrogenerated Mediatorssupporting
confidence: 84%
See 1 more Smart Citation
“…Work conducted in our laboratory involved the catalytic degradation of CFC-113 in the presence of electrogenerated cobalt(I) salen [39] in a DMF-TBABF 4 medium saturated with CO 2 ; recently, we have finished an unpublished study pertaining to the use of electrogenerated nickel(I) salen in DMF-TBABF 4 saturated with CO 2 . Like the results found by Titov et al [37], negligible amounts of carboxylic acids were detected upon reduction of this vicinal CFC, but higher yields of more dechlorinated products (HFC-1132 and HFC-1132a) were obtained; these observations suggest the possibility that CO 2 mediates electron transfer to cause more effective cleavage of carbon-chlorine bonds. Direct reduction of CFC-113 in the presence of CO 2 at a glassy carbon cathode gives rise to a single cathodic peak, as opposed to the two peaks recorded for direct reduction of CFC-113 in the absence of CO 2 .…”
Section: B Catalytic Reduction Of Cfcs With Electrogenerated Mediatorssupporting
confidence: 84%
“…Using several different nickel(I) species (with azamacrocyclic and bipyridine ligands) that were electrogenerated at a platinum cathode, Titov et al [36] demonstrated that the catalytic degradation of CFC-113 in DMF-TBABF 4 is a feasible undertaking; the proposed reaction scheme involves interaction of the substrate with a nickel(I) complex to form a nickel(III)organohalogen intermediate that immediately undergoes reduction to afford CFC-1113 in an overall two-electron process, after which CFC-1113 is converted to HFC-1123 in almost 100% yield. Titov and co-workers [37] examined the reduction of geminal and vicinal CFCs at glassy carbon and silver cathodes in the presence of SO 2 and CO 2 . In the case of geminal CFCs, such as CFC-113a, SO 2 acts both as a reagent and an electron-transfer mediator to form CF 3 CCl 2 SO 2 and HCFC-123 at a potential 1.3 V more positive than in the absence of SO 2 .…”
Section: B Catalytic Reduction Of Cfcs With Electrogenerated Mediatorsmentioning
confidence: 99%
“…For example, Freon conversion can be used for the synthesis of many fluorine-containing compounds, including halogenated olefins, 7 carboxylic or sulfonic acids, aldehydes, and ketones. 8,10,11 Metal-catalyzed dehalogenation of organic compounds has also been considered as a method for pollutant elimination from water. 12 The catalytic action of a metal complex in a reductive process involves a stage of electron acceptance by the catalyst (catalyst reduction), followed by substrate reduction by the reduced form of the catalyst (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%